PENINGKATAN KEMAMPUAN MENULIS TEKS EKSPLANASI DENGAN PENDEKATAN COLLABORATIVE LEARNING MENGGUNAKAN PADLET: (Systematic Literature Review) - Lazuardi, Ahmad; Aniyatussaidah; Ramlan Rosyad (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2023)
Writing can be described as one of the components of education to be able to develop useful abilities. Writing as a component of useful skills is the articulation of language used to convey reflections or thoughts in the form of letters, images and words to readers. Writing is the most difficult skill to master compared to the other three skills, especially listening, reading and speaking. The aim of this study is to examine the role of the Padlet application in increasing the ability to write explanatory text by applying a collaborative learning approach. The study methodology applied in this study is a systematic literature review by collecting reading material from various scientific articles and then comparing hypotheses and study findings, which are analyzed descriptively. Obtaining a literature review from 19 scientific articles indexed by SINTA, and SCOPUS, it was found that the Padlet application was able to improve the ability to write explanatory text using a collaborative learning approach. Apart from that, this article also included studies regarding digital teaching materials, Padlet applications, collaborative learning, and explanatory text.